Corruption In The Legal Views Of Baharuddin Lopa And Artidjo Alkostar From The Perspective Of Criminal Law And Islamic Law - Medi Animan (UIN Siber Syekh Nurjati Cirebon, 2024)
Corruption in Indonesia has become a fundamental problem and has even become so deeply rooted that it is difficult to eradicate. This can be seen in Indonesia‟s increasingly widespread criminal acts of corruption. This research aims to discover the law enforcement principles of Baharuddin Lopa and Artidjo Alkostar, as well as the views of Islamic law on corruption. The research method used is qualitative research. The results of this study are as follows: first, Baharuddin Lopa is a prosecutor who consistently fights for the eradication of corruption in Indonesia through a brilliant breakthrough, namely the principle of reverse proof, or the defendant must prove that his property is halal or legal. In upholding justice, Baharuddin Lopa holds the principles of religion, integrity, and spirit. Artidjo Alkostar started his career as a Supreme Court Justice in 2000 and retired on 22 May 2018. Artidjo‟s work as a Supreme Court judge is notable because he dared to differ from the other judges in the case of former President Soeharto and the Bank Bali scandal with the defendant Djoko Soegiarto Tjandra. Second, corruption in Islam is an act that violates Sharia. In the context of broader Islamic teachings, corruption is an act that contradicts the principles of justice (al-Adalah), accountability (al-amanah), and responsibility. Corruption, with all its negative impacts, can cause various distortions to the life of the state and society.